The international encyclopedia of revolution and protest 1500 to the present - Ness, Immanuel (Gale virtual reference library, 2009)
Covers the history of protest and revolution over the past 500 years. Provides scholars and teachers and students with the information needed to understand the role and significance and origin of protest and revolution from 1500 to the present.